The effect of omega-3 fatty acids and vitamin E supplementation on lipid profiles and inflammatory markers in hemodialysis patients: A systematic review of current literature - Meliana, Ahila; Afizah, Ameilia Anastasya Rahma; Hasanatuludhhiyah, Nurina (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2023)
ABSTRAK Latar Belakang: Kebutuhan terapi hemodialisis (HD) masih terus berkembang. Di Indonesia, HD mewakili 82% dari pelayanan cuci darah di Puskesmas Indonesia. Namun, HD menyebabkan peningkatan penanda inflamasi serta perubahan profil lipid. Kombinasi vitamin E dan asam lemak omega-3 dapat membantu mengurangi indikator inflamasi dan meningkatkan profil lipid.Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh co-suplementasi vitamin E dan omega-3 terhadap profil lipid dan indikator inflamasi.Metode: Penelitian ini dilakukan di PubMed dan Google Scholar untuk mencari artikel-artikel secara sistematis, Kriteria inklusi yang digunakan adalah artikel bahasa Inggris dengan uji coba terkontrol acak (RCT) dan uji coba terkontrol (CT) yang menyelidiki efek vitamin E dan omega-3 pada profil lipid dan penanda inflamasi pasien hemodialisis. Semua artikel harus diterbitkan antara September 2013 - September 2022. AM dan AA melakukan seluruh proses penelitian sebagai reviewer dan seluruh ketidaksetujuan diselesaikan bersama NH sebagai penulis ketiga.Hasil: 1020 studi diidentifikasi dari database dan 12 artikel terpilih berdasarkan kriteria inklusi. Asam lemak omega-3 meningkatkan profil lipid, seperti kolesterol, LDL, HDL, dan trigliserida. Namun, studi ini hanya menemukan satu penelitian tentang efek vitamin E pada profil lipid. Asam lemak Omega-3 dan suplementasi vitamin E tidak memiliki efek signifikan pada penanda inflamasi, tetapi dampak suplementasi vitamin E pada tingkat IL-6 telah dilaporkan.Kesimpulan: Co-suplementasi Omega-3 dan vitamin E berpengaruh pada penurunan level indikator inflamasi dan profil lipid pasien hemodialisis. Kami merekomendasikan bahwa studi berikutnya harus berfokus pada penelitian uji klinis mengenai pengaruh suplementasi kombinasi ini terhadap indikator inflamasi dan profil lipid pasien hemodialisis. KATA KUNCI: hemodialisis; indikator inflamasi; omega-3; profil lipid; vitamin E ABSTRACTBackground: Hemodialysis therapy (HD) demands is still growing. In Indonesia, HD represents 82% of dialysis services in Indonesian health centers. However, HD causes an increase in inflammatory markers as well as lipid profile changes. The combination of vitamin E and omega-3 fatty acids can assist to decrease inflammatory indicators and enhance lipid profiles.Objectives: This study aims to investigate the effect of co-supplementation of vitamin E and omega-3 on lipid profiles and indicators of inflammation.Methods: This study was conducted on PubMed and Google Scholar to search articles systematically. The inclusion criteria used were English articles of randomized controlled trials (RCTs) and controlled trials (CT) that investigated the effects of vitamin E and omega-3 on lipid profiles and inflammatory markers of hemodialysis patients. All articles must be published between September 2013 - September 2022. AM and AA conducted the entire research process as reviewers and all disagreements were finalized with NH as a third author.Results: 1020 studies were identified from databases. Afterward, this study included 12 articles based on the inclusion criteria. Omega-3 fatty acids improve lipid profiles, such as cholesterol, LDL, HDL, and triglyceride. While we only found a single study about the effect of vitamin E on lipid profile. Furthermore, omega-3 fatty acids and vitamin E supplementation have no significant effect on inflammatory markers, but the impact of vitamin E supplementation on IL-6 levels was reported.Conclusions: Co-supplementation of omega-3 and vitamin E decrease levels of inflammatory indicators and lipid profiles in hemodialysis patients. We recommend that future studies should focus on clinical trials to investigate the effect of this co-supplementation on lipid profiles and inflammatory markers of hemodialysis patients. KEYWORD: hemodialysis; inflammatory markers; lipid profiles; omega-3, vitamin E